1983
DOI: 10.1254/jjp.33.267
|View full text |Cite
|
Sign up to set email alerts
|

KC-404: A potential anti-allergic agent with antagonistic action against slow reacting substance of anaphylaxis.

Abstract: Abstract-The mode of action of a novel compound, 3-isobutyryl-2-isopropylpyrazolo [1,5-a]pyridine (KC-404), as a potential anti-allergic agent has been investigated. KC 404 was shown to have a direct bronchodilator activity in guinea pig trachea in vitro and in anesthetized guinea pig in vivo. In addition, KC-404 had a fairly selective antago nistic action against slow reacting substance of anaphylaxis (SRS-A) on guinea pig ileum in vitro. In anesthetized guinea pigs, ED50 values for intravenously and intraduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Mong et al, 1987b;Ahnfelt-R0nne et al, 1988). Ibudilast is a novel, orally active anti-asthmatic that is in clinical use (Nishino et al, 1983). The drug inhibits the increase in vascular permeability induced by antigen in sensitized guinea-pig airway smooth muscle (Eda et al, 1987) and antagonizes LTD4-induced contraction of guinea-pig lung parenchymal and tracheal strips (Ohasi et al, 1986).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Mong et al, 1987b;Ahnfelt-R0nne et al, 1988). Ibudilast is a novel, orally active anti-asthmatic that is in clinical use (Nishino et al, 1983). The drug inhibits the increase in vascular permeability induced by antigen in sensitized guinea-pig airway smooth muscle (Eda et al, 1987) and antagonizes LTD4-induced contraction of guinea-pig lung parenchymal and tracheal strips (Ohasi et al, 1986).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…KC-404 is shown to be a potent inhibitor of SRS-A released from guinea pig lung fragments [6] and a se lective antagonist of LTD4 [7], In addition to these anti-allergic actions, KC-404 has cerebrovasodilating activity and selectively increases vertebral blood flow when compared with femoral blood flow in anesthe tized dogs [12]. But there are no reports about the ef fect of KC-404 to the release of LTs.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, KC-404 prefe rentially inhibited SRS-A-induced contraction of isolated guinea pig ileum, SRS-A-induced bronchoconstriction in anesthetized guinea pig and SRS-A-induced increase in cutaneous vascular permeability in rats and guinea pigs [6]. Later it was suggested that KC-404 is a selective antagonist of LTD4 and that it interacts with LTD4 receptor in airway smooth mus cles but not in ileum [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical uses are based on the ability of ibudilast to relax airway smooth muscle, 13) attenuate allergic reaction, [13][14][15][16] inhibit the aggregation of platelets, 15,16) and increase cerebral blood flow [17][18][19][20] mainly through inhibition of phosphodiesterases (PDEs). 21,22) A previous study demonstrated that 2-week administration of ibudilast shortened the mean retinal circulation time in patients with diabetes mellitus.…”
mentioning
confidence: 99%